Analisis Performans Reproduksi Sapi Bali Betina Berdasarkan Umur dan Kondisi Tubuh - Satriawan Satriawan (Journal of Animal Husbandry, 2025)
This study aims to analyze the reproductive performance of female Bali cattle based on age and body condition score (BCS). The research was conducted at a community-based cattle breeding center in Bali Province from January to June 2025. Data were collected through direct observation and interviews with breeders, focusing on parameters such as age at first mating, calving interval, conception rate, and postpartum estrus. The collected data were analyzed using descriptive statistics and correlation analysis to determine the relationship between body condition and reproductive efficiency. The results showed that cows with an optimal BCS (score 3–3.5) had better reproductive performance, shorter calving intervals, and higher conception rates compared to those with low (<2.5) or excessive (>4) body condition. Age also significantly affected reproductive traits, where cows aged 4–7 years exhibited the best reproductive performance. It can be concluded that maintaining an optimal body condition and appropriate age management plays a crucial role in improving the reproductive efficiency of Bali cattle.